The Cross-Sectional Study of Self Efficacy, Diet Compliance, and Blood Sugar Levels on Diabetes Mellitus Patients in Indonesia - Dafriani, Putri; Marlinda, Roza; Prameswari, Mahira; Sari Dewi, Ratna Indah; Yuniko, Fajrilhuda (Journal of Pharmacy and Nutrition Sciences, 2022)
Diabetes mellitus (DM) has become a global health problem because the prevalence of diabetes mellitus continues to increase. Data from the West Sumatra Provincial Health Office (2018), DM cases totalled 44,280 cases, with a DM prevalence of 1.6% in 2018. Self-efficacy plays an important role in controlling blood sugar levels. Lack of self-efficacy causes the patient's blood sugar levels to become abnormal, resulting in a risk of complications. This research aims to study the relationship between self-efficacy and diet compliance with blood sugar levels in DM patients at the Andalas Public Health Center, Padang City. The research method is descriptive-analytic with a cross-sectional approach, with a total sample of 75 people. The results showed that 78.7% of the respondents have hyperglycemia, 72.0% with non-compliant to their diet limitation, and 68.0% with low self-efficacy. A relationship exists between diet compliance and blood sugar levels in type 2 DM patients. There is a relationship between self-efficacy and blood sugar levels in type 2 diabetes mellitus patients at the Padang Andalas Public Health Center in 2022.